Interrelation Between Ionic Conduction and Ions Fraction of Biopolymer Electrolytes Based on Alginate Doped With NH4Cl - N. M., Khan; N. F., Mazuki; A. P. P., Abdul Majeed; A. S., Samsudin (Taylor and Francis, 2021)
In this report, the relationship between the ionic conduction properties of alginate (AL) based biopolymer electrolyte (BE), and the amount of NH4Cl dopant and ethylene carbonate (EC) plasticizer is discussed. The BE was prepared via a solution casting method and characterized by using Fourier transform infrared (FTIR) and electrical impedance spectroscopy (EIS), respectively. The highest ionic conductivity attained for the AL-NH4Cl BE was 3.18 × 10−8 S cm−1 for 8 wt.% of NH4Cl. Nonetheless, an increased optimum value of 1.46 × 10−6 S cm−1 was obtained when plasticized with 4 wt.% of EC. It was observed that with the addition of the EC content between the range of 1 wt.% and 7 wt.% into the AL-NH4Cl with 8 wt.% salt content increased the flexibility of the AL chains to facilitate free H+ ion transport. The weak bonding created through EC - NH4+ allows higher dissociation of proton ions (H+), allowing more interaction to occur on the AL polymer backbone. These ions will hop from one complex site of AL to another, as revealed by FTIR analysis. Through the deconvolution analysis of the BE systems, it was demonstrated that the ionic conductivity for both systems was governed by the enhancement of the free ions fraction which, in turn, increased the number of mobile ions upon the addition of NH4Cl.